Modernism Poetic of Abou Tammam from the Perspective of Ancient Arab Criticism. _Language Criticism Model - Boudjerra, Samira_ (Milev Journal of Research and Studies, 2019)
linguistic Arabic critics and the modern poetry of Abou Tamam. They were the first to receive the modernity of About Tamam and provide their jujments which contributed in clarifying some critical concepts that are included in the core of hritecal Arabic poetry.